Maestros del ritmo con addendum - Ma, Eve A.; Izquierdo, Lalo; Medrano Cotito, Juan; Lobato n, Freddy; Palomino Productions ([Berkeley, California] : Palomino Productions, 2017)
Three of Peru's finest masters of Afro-Peruvian music (Lalo Izquierdo, Cotito and Huevito) play the cajo n, sing, dance, and shoot the breeze about their childhood and their roots. Well-known guitarist Coco Linares and others accompany them in the performance part of the documentary--
Originally released as a motion picture in 2017
Starring Lalo Izquierdo, Juan Medrano Cotito, Freddy Huevito Lobato n, Coco Linares, Leticia Coray Merino.
Cinematographer, Luis Cateriano Nanrique, Eve A. Ma ; editor, Eve A. Ma.
In Spanish. Also available with English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 2, 2018)
Keywords: Percussionists -- Peru; Music -- Peru -- African influences; Dance -- Peru -- African influences; Popular music -- Peru; Blacks -- Peru -- Music; Documentary films; Nonfiction films; Internet videos; Streaming video